Hematological manifestations of systemic lupus erythematosus in the early stage: association with other symptoms of the disease and possible prognostic value - A. V. Petrov; V. A. Beloglazov; D. V. Shadyro; A. R. Gafarova; A. A. Petrov (Научно-практическая ревматология)
Objective: to assess the relationship between hematological manifestations of systemic lupus erythematosus (SLE) in the early stage of the disease and development of other syndromes and symptoms of the disease, as well as the nature and severity of internal organs damage during the subsequent five-year period.Subjects and methods. The analysis of data of examination of 89 patients with SLE during the five-year period was carried out. The frequency of clinical manifestations of SLE, the level of antinuclear and antiphospholipid antibodies, SLICC/ACR damage index (SDI) depending on the presence of hematological manifestations of SLE in the onset of the disease including leukopenia (LP), thrombocytopenia (TP) and autoimmune hemolytic anemia (AGA) were studied.Results and discussion. In the onset of SLE LP was observed in 21.3%, TP – in 26.9%, AGA – in 8.9% of patients. The presence of LP was associated with an increase of antibodies to SSA frequency, and TP – with more frequent detection of antibodies to Ro-52, cardiolipin and β-2-glycoprotein (p<0.05). Patients with TP in the onset of SLE compared with patients without hematological manifestations, had an increase (p<0.05) of the cumulative incidence of nephritis (83.3 and 42.9%), central nervous system lesions (70.8 and 26.5%), vasculitis (45.8 and 10.2%) and Libman-Sachs endocarditis (20.8 and 6.1%, respectively), which was accompanied by an increase of SDI values (median was 2.09 [2, 1.82; 2.21] and 1.12 [0.81; 1.32], p<0.05). In patients with LP, the cumulative incidence of pneumonitis and Sjogren's syndrome was increased in the onset of SLE compared with patients without hematological manifestations (15.8 vs 6.1% and 15.7 vs 2.0%, respectively, p<0.05).Conclusion. Presence of TP in the onset of SLE is a predictor of kidneys, central nervous system, peripheral vessels and heart valves damage during the next 5 years.